Madagascar Economic Update, April 2010 : Whats Going On? - World Bank (Washington, DC, 2017)
After one year of political crisis, uncertainty remains the key word. Private activities have rebounded compared to the first quarter 2009 but are still far from their pre-crisis levels. Fiscal policy, globally cautious, went to several 'stop and go' episodes, sending mixed messages to financial markets, especially visible through the recent variations in the exchange and interest rates. This uncertainty is exacerbated byt the lack of consistency in policy decisions.